Chapter 12 The power of place and perspective Sensory media and situated simulations in urban design - Liestøl, Gunnar (Changing Mobilities, 2014)
Mobilities has become an important framework to understand and analyze contemporary social, spatial, economic and political practices. Especially as mobile media become seamlessly integrated into transportation networks, navigating urban spaces, and connecting with social networks while on the move, researchers need new approaches and methods to bring together mobilities with mobile communication and locative media. Mobile communication scholars have focused on cell phones, often ignoring broader connections to urban spaces, geography, and locational media. As a result, they emphasized virtual mobility and personalized communication as a way of disconnecting from place, location and publics. The growing pervasiveness of location-aware technology urges us to rethink the intersection among location, mobile technologies and mobility. Few studies have addressed the many transformations taking place in mobile sociality and in urban spatial processes through the appropriation of these technologies. Chapter 12 of this book is freely available as a downloadable Open Access PDF under a Creative Commons Attribution-Non Commercial-No Derivatives 3.0 license. https://s3-us-west-2.amazonaws.com/tandfbis/rt-files/docs/Open+Access+Chapters/9781138778139_oachapter12.pdf